2021
DOI: 10.1097/cad.0000000000001171
|View full text |Cite
|
Sign up to set email alerts
|

Treatment response to eribulin and anlotinib in lung metastases from rare perianal adenoid cystic carcinoma: a case report

Abstract: Adenoid cystic carcinoma (ACC) is a rare salivary glands tumor and often displays aggressive behavior with frequent relapse and metastasis. The terminal ACC lacks standard treatment guidelines and is always accompanied by poor prognosis. Here, we report a case of rare perianal ACC who received resection and palliative adjuvant radiation. Five years later, PET-computed tomography (CT) showed perianal recurrence and multiple pulmonary metastases. Combined chemotherapy with doxorubicin, carboplatin and cyclophosp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 28 publications
0
5
0
Order By: Relevance
“…This indicates that TP53 might be a potential therapeutic target in patients with ACC. Additionally, in one reported case, an ACC patient with a BCL-6 corepressor mutation experienced significant inhibition of his disease after combination treatment with eribulin and anlotinib ( 46 ), which provides a certain basis for the use of this combination in treating ACC and emphasizes the need to find new therapeutic targets for ACC.…”
Section: Review and Discussionmentioning
confidence: 99%
“…This indicates that TP53 might be a potential therapeutic target in patients with ACC. Additionally, in one reported case, an ACC patient with a BCL-6 corepressor mutation experienced significant inhibition of his disease after combination treatment with eribulin and anlotinib ( 46 ), which provides a certain basis for the use of this combination in treating ACC and emphasizes the need to find new therapeutic targets for ACC.…”
Section: Review and Discussionmentioning
confidence: 99%
“…Nevertheless, prolonged progression-free survival (PFS) upon axitinib treatment was observed in MYB-NFIB-positive patients [155] . Sorafenib also exhibited considerable responses and prolonged stable disease in ACC patients [156,157] . The combination of anlotinib with the tubulin binder eribulin showed an enduring response in a MYB-NFIB and BCOR (BCL6 corepressor) mutant ACC patient after chemotherapy (carboplatin, cyclophosphamide, doxorubicin) had failed [158] .…”
Section: Kinase Inhibitorsmentioning
confidence: 97%
“…Sorafenib also exhibited considerable responses and prolonged stable disease in ACC patients [ 156 , 157 ] . The combination of anlotinib with the tubulin binder eribulin showed an enduring response in a MYB-NFIB and BCOR (BCL6 corepressor) mutant ACC patient after chemotherapy (carboplatin, cyclophosphamide, doxorubicin) had failed [ 158 ] . A phase 2 trial of anlotinib in metastatic ACC revealed activity and controllable toxicity, indicating a possible application as palliative therapy of advanced ACC [ 159 ] .…”
Section: Myb Proteins and Cancer Drug Resistancementioning
confidence: 99%
“…So VEGFR signal inhibition in the tumour may be useful in suppressing the tumour growth and blood flow [29,73,74]. Anlotinib, a tyrosine kinase inhibitor against VEGFR-1,-2,-3, and Lenvatinib, a multiple kinase inhibitor against VEGFR-1,-2,-3 kinases have shown effective results as a molecular target therapy for AdCC [72, 75,76].…”
Section: Treatmentmentioning
confidence: 99%